PERANCANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MATA PELAJARAN IPA MATERI UNSUR SENYAWA DAN CAMPURAN KELAS VIII SMP NEGERI 7 SURAKARTA - Surendro, Ryo; Supeni, Siti; Maria Sofia Hapsari, Alfonsa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study uses the Research and Development (R&D) method with the ADDIE development model. The techniques used for data collection include interviews, questionnaires and documentation and are equipped with system testing procedures. Blackbox Testing techniques and validation of product feasibility by experts were carried out to obtain responses regarding the feasibility of learning media. The validation results for product feasibility were analyzed and then converted using a Likert Scale. The objectives of this study are: 1) To determine and assess the level of feasibility of the design of android-based learning for the subject of science, the material of elements, compounds and mixtures for class VIII of SMP Negeri 7 Surakarta; 2) To determine the responses of teachers regarding the design of android-based learning for the subject of science, the material of elements, compounds and mixtures for class VIII of SMP Negeri 7 Surakarta. The results of the study showed that the learning media